Color Enrichment to Use of Plant Leaves in Eco Printing "An Applied Study" - Ruaa Ali Jebur; Assad Jawad Abdmuslim (الاكاديمي)
The current study is concerned with the color enrichment of plant leaves in environmental printing because of their aesthetic and artistic values that work to achieve the expressive dimension in graphic works.  The research included four chapters. The first chapter contained the research problem, the importance of the research, the need for it, and the goal of the research, which includes: producing graphic works by employing plant leaves with various color effects using environmental printing technology. The first chapter also contained the limits of the research and definition of terminology. The second chapter included the theoretical framework and previous studies, which contained two sections. The first section included color and its physical effect. The second section included environmental printing, its techniques and characteristics, while the third chapter included research procedures that included the research community, its sample, and the methodology. Research in addition to forming models using environmental printing technology. The fourth chapter included the results of the research, the most important of which are: